2013
DOI: 10.1007/s00266-013-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Latissimus Dorsi Muscle Flap for Breast Reconstruction After Skin-Sparing Total Mastectomy: Report of 14 Cases

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…Endoscopic non-robotic LDFR was reported in several studies [4][5][6][7][8], and in 2007, Missana et al reported a study including 52 patients [4] and more recently by others with smaller series [6][7][8]. Nakajima et al [8] reported a study with 168 LDF video-assisted reconstructions but only for reconstruction after partial mastectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic non-robotic LDFR was reported in several studies [4][5][6][7][8], and in 2007, Missana et al reported a study including 52 patients [4] and more recently by others with smaller series [6][7][8]. Nakajima et al [8] reported a study with 168 LDF video-assisted reconstructions but only for reconstruction after partial mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Development of robotic surgery since several years was very important for prostatic cancer, gynecologic cancer, colo-rectal cancer, and thoracic and thyroid surgery [1][2][3]. Endoscopic non-robotic latissimus dorsi-flap breast reconstruction (LDFR) has been reported in several studies [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these findings were consistent with the results from previous studies evaluating satisfaction. 8,16,17,[27][28][29] According to some authors, mastectomy can cause low self-esteem and body image issues. Therefore, reconstruction is indicated for patients requiring mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional open technique requires a 15 to 30 cm dorsal incision. Endoscopic LDF has been proposed and achieved in some centers, 18-27 but this surgical procedure is not easy with nonflexible endoscopic instruments and a 2-dimensional view.…”
Section: Introductionmentioning
confidence: 99%